Comprehensive discrete mathematics and structures - Gupta, Satinder Bal (Laxmi Pub., 2004)
Comprehensive discrete mathematics and structures / Gupta, Satinder Bal. -- Kolkata: Laxmi Pub., 2004 511.3 G978 No. of Copies : 1